"Here, your only relative is money..." why slum social networks do not facilitate neighborhood community development: insights through a sanitation lens - Japheth Nkiriyehe Kwiringira; Joseph Rujumba; Paulino Ariho; James Mugisha; Henry Zakumumpa; Elizabeth W Perry Mohling; Mathias Akugizibwe; Innocent Kamara Tumwebaze; Charles Onyutha (BMC, 2023)
Abstract Introduction Though social networks which are deemed vehicles of community development exist in slum areas, underdevelopment still persists in these areas. We explored the nature and role of social networks in facilitating community development in the slums of Kampala through a sanitation lens. Methods Qualitative Social Network Analysis (SNA) was done to understand the nature of slum social networks primarily through the analysis of sanitation behavior. Data were collected through six Focus Group Discussions (FGD), six In-depth Interviews (IDIs), and 18 Key Informant Interviews (KII) with Government, civil society and private stakeholders. We used both inductive and deductive thematic analysis. Results Four themes emerged in our analysis; i); Unsupportive environments, uncooperative neighbours and uncertainty of tenure: participants reported slums as unsupportive of community development due to a shortage of space, poverty and unplanned services. Tenants perceived landlords as exploitative and predatory and wished the tables are turned. This notion of cyclic exploitation did not encourage collective action for community good. Short-term economic survival trumped long-term community interests ii) Patronage and poor service delivery: varying degrees of patronage led to multiple forms of illegalities and violations such as tax evasion. Due to vested interests and corruption among public officials, the slum population was lethargic. iii) Intersecting realities of poverty and unemployment: slum dwellers lived on the margins daily. Hence, poor living conditions were a secondary concern. iv) Social relations for personal development: Slum social networks were driven by individual interests rather than community good. Slum dwellers prioritized connections with people of common socio-economic interests. As such social networks were instrumental only if they 'added value'. Conclusion Social networks in slums are only concerned about survival needs. Slums require responses that address the complexity of slum formation and broader livelihood challenges, as well as re-assessing the meaning of community. We posit that more needs to be done in understanding the meaning and workings of a sociology beyond physical societies. Poverty is a modifier of social systems and processes and should be a concern for all stakeholders involved in slum development.